Edukasi Kenakalan Remaja dan Keselamatan Berkendara pada Siswa SMP Negeri 2 Tujuh Belas Kabupaten Bengkayang - Dinda Dwi Prasetiyani; Eksa Rusdiyana; Sudibya Sudibya; Alit Adi Saputra; Dinda Putri Permatasari; Luthfiana Rihadatul ‘Aisy; Muhammad Ezzat Alfauzi; Moh Sayful Zuhri; Muhamad Najib Shofy (Jurnal Informasi Pengabdian Masyarakat, 2023)
Adolescence is known as a period of change from child to adult. In this era, many teenagers are unable to withstand all the regulations that take away their freedom. Lack of mental stability during adolescence also affects driving safety, especially if conditions and circumstances force teenagers to drive motorized vehicles as the main transportation to school even though they are still underage. This is the reason for implementing Juvenile Delinquency and Driving Safety Education activities at Negeri 2 Seventeen Junior High School (SMP), Bengkayang Regency. The method for implementing this activity is in the form of counseling. This educational program is carried out offline by presenting the material through lectures or interactive lectures and discussions. As a result of this activity, it is hoped that students will understand and crystallize how to socialize positively and the importance of being aware of safety when driving. It is hoped that the results of this service activity will become basic capital in forming the character of students in school and society.